2020
DOI: 10.2337/dc20-0882
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Continuous Glucose Monitoring During a Hyperinsulinemic-Hypoglycemic Clamp Significantly Underestimates the Degree of Hypoglycemia

Abstract: Figure 1-Glucose data (mean 6 SEM) during hyperinsulinemic-hypoglycemic clamps. Black circles represent AV plasma glucose; blue squares, AV blood tested via SMBG; red triangles, CGM. ***P , 0.001. care.diabetesjournals.org Farrell and Associates e143

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Here, unlike the common definition for level 1 hypoglycemia based on the threshold of 70 mg/dL, we instead choose 80 mg/dL as the hypoglycemia threshold. This is because recent results by Farrell et al 57 have revealed a measurement artifact, i.e., that the real-time continuous glucose monitoring (CGM), where we would expect these algorithms to have clinical applicability, underestimates the degree of hypoglycemia by a difference of 10 mg/dL, as shown in Supplementary Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, unlike the common definition for level 1 hypoglycemia based on the threshold of 70 mg/dL, we instead choose 80 mg/dL as the hypoglycemia threshold. This is because recent results by Farrell et al 57 have revealed a measurement artifact, i.e., that the real-time continuous glucose monitoring (CGM), where we would expect these algorithms to have clinical applicability, underestimates the degree of hypoglycemia by a difference of 10 mg/dL, as shown in Supplementary Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“…(%) 21 (52.5) Body compositions Body mass, kg 81.0 (71.3, 94.2), 84.1 ± 18.7 Height, m 1.64 (1.59, 1.73), 1.66 ± 0.10 BMI, kg/m 2 29.7 (26.6, 33.1), 30.1 ± 5.1 Hormone levels Cortisol, μg/dL 15.9 (13.0, 20.2), 16.1 ± 6.0 Leptin, ng/dL 19.8 (9.57, 31.1), 23.0 ± 17.8 Fasting glucose, mg/dL 117.5 ± 17.9 Insulin, μIU/mL 13.33 ± 13.29 HOMA1-IR 3.51 ± 3.47 Blood glucose data brief Data reading length (h) 90 (82, 170), 117 ± 63 Model input BG length (min) 30 Hypoglycemia threshold (mg/dL) 80 Hyperglycemia threshold (mg/dL) 180 HbA1c (%) 7.33 ± 1.31 HOMA1-IR the homeostatic model assessment index for insulin resistance. We choose 80 mg/dL as the hypoglycemia threshold, because recent results by Farrell et al 57 have revealed a measurement artifact, i.e., that the real-time CGM underestimates the degree of hypoglycemia by a difference of 10 mg/dL, as shown in Supplementary Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether a stricter criterion is necessary for patients unable to master the technology entirely is a question to address in future investigations. It is worth noting that increasing evidence has shown that CGM underestimates the degree of hypoglycemia, suggesting that CGM may worsen the severity and delay the treatment of hypoglycemia [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… 48 50 One issue emerging for CGM and FGM is that both devices are less accurate during hypoglycaemia (e.g. Freckmann et al and Farrell et al 51 , 52 ), and may therefore not detect all hypoglycaemic events. This may explain why they have not been shown in clinical trials to improve hypoglycaemia awareness.…”
Section: Technologymentioning
confidence: 99%